2014
DOI: 10.1111/jph.12359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fusarium culmorum Tri Gene Transcription on Deoxynivalenol and D3G Levels in Two Different Barley Cultivars

Abstract: Fusarium culmorum is a phytopathogenic fungus causing Fusarium head blight (FHB), which negatively affects cereals by producing mycotoxins, such as deoxynivalenol (DON). In this work, two barley cultivars, Chevron and Pedant, with different degrees of resistance to FHB were inoculated with F. culmorum. The transcription levels of the Fusarium Tri genes and barley UDP‐glycosyltransferase genes were investigated. The amounts of pathogen, DON and the detoxification product deoxynivalenol‐3‐O‐glucoside (D3G) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…In germination process, when seeds try to survive, transformed D3G can increase more, even to 3:1 ratio (Figure 1a, wheat). D3G levels depend on ability of cereal genotype transform DON to D3G, as confirmed Faltusová et al (2015) from comparison of susceptible and more resistant cultivars. Plant breeders consider this ability as a key trait for resistance of genotypes to Fusarium in breeding (Shin et al 2012).…”
Section: Resultsmentioning
confidence: 87%
“…In germination process, when seeds try to survive, transformed D3G can increase more, even to 3:1 ratio (Figure 1a, wheat). D3G levels depend on ability of cereal genotype transform DON to D3G, as confirmed Faltusová et al (2015) from comparison of susceptible and more resistant cultivars. Plant breeders consider this ability as a key trait for resistance of genotypes to Fusarium in breeding (Shin et al 2012).…”
Section: Resultsmentioning
confidence: 87%
“…These factors such as weather conditions around flowering, pathogen virulence and agricultural practices (crop rotation, soil cultivation, fertiliser, chemical treatment) were summarised by Edwards (2004). This work and our previous study examining two barley cultivars differing in Fusarium resistance (Faltusová et al 2015) suggest some ability of the host to delay transcription of the pathogen's Tri genes. We expect that further deeper examination of the Tri gene regulation transcription could help to find possibilities of decreasing mycotoxin production by Fusarium.…”
Section: Discussionmentioning
confidence: 98%
“…Transcription of Fusarium Tri genes Tri4 and Tri5 was greater in the most infected cultivars Nordus and Diplom, and this observation is consistent with the high DON content in these cultivars. In the case of regulatory genes, transcription differed between 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 (Faltusová et al 2015) and with that of Kumaraswamy et al (2011), who concluded in agreement with Boutigny et al (2009) that the D3G/DON ratio may not correctly identify the mechanisms of resistance inasmuch as the DON reduction can be due both to DON conversion to D3G and its reduced synthesis. Resistance based on a modification of trichothecenes is important in terms of the plant's own resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation